Signalling pathways and the regulation of SUMO modification. (23rd November 2007) - Guo, B.; Yang, S.-H.; Witty, J.; Sharrocks, A.D.
Abstract : The modification of proteins by SUMO (small ubiquitin-related modifier) conjugation is becoming increasingly recognized as an important regulatory event. Protein SUMOylation can control a whole range of activities, including subcellular localization, protein–protein interactions and enzymatic activity. However, the SUMOylation process can itself be controlled. In the present review, the mechanisms through which protein SUMOylation is regulated are discussed, with particular emphasis on the impact of signalling pathways. A major point of regulation of the SUMO pathway is through targeting the E3 ligases, and a number of different ways to achieve this have been identified. More generally, the MAPK (mitogen-activated protein kinase) pathways represent one way through which SUMOylation of specific proteins is controlled, by using molecular mechanisms that at least in part also function by modifying the activity of SUMO E3 ligases. Further intricacies in signalling pathway interactions are hinted at through the growing number of examples of cross-talk between different post-translational modifications and SUMO modification.